Direct determination of the surface tension of metal alloys near the melting point by means of the generation of spherical microparticles in uniform electric fields - Cirilo, Diego Julio; Greco, Alejandro Cesar; Versaci, Raul Antonio (IOP Publishing, 2021)
Fil: Cirilo, Diego Julio. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Física del Plasma. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Física del Plasma; Argentina. Comisión Nacional de Energía Atómica. Centro Atómico Constituyentes; Argentina. Joint Institute for Nuclear Research; Rusia